A pyrene-armed hexahomotrioxacalix[3]arene as a multi-sensor via synergistic and demetallation effects. Issue 52 (30th December 2015) - Jin, Cheng-Cheng; Fukuda, Mizuho; Wu, Chong; Jiang, Xuekai; Ni, Xin-Long; Zeng, Xi; Redshaw, Carl; Yamato, Takehiko
Abstract: A new pyrene-armed hexahomotrioxacalix[3]areneL has been synthesized, which exhibits a pronounced fluorescence enhancement response toward Cu 2+ ions via a Zn 2+ or Cd 2+ triggered synergistic effect. Additionally, theL ·Cu 2+ complex can subsequently serve as a sensor for F − via anion-induced demetallation. The fluorescence responses by the input of Cu 2+, Zn 2+ /Cd 2+ and F − can be constructed as a combinational logic gate which mimics a set of molecular traffic signals. Graphical abstract: